CMV-Specific CD8 T Cell Differentiation and Localization: Implications for Adoptive Therapies - Smith, Corinne J.; Quinn, Michael; Snyder, Christopher M. (Frontiers in Immunology, 2016)
Human cytomegalovirus (HCMV) is a ubiquitous virus that causes chronic infection, and thus is one of the most common infectious complications of immune suppression. Adoptive transfer of HCMV-specific T cells has emerged as an effective method to reduce the risk for HCMV infection and/or reactivation by restoring immunity in transplant recipients. However, the CMV-specific CD8+ T cell response is comprised of a heterogenous mixture of subsets with distinct functions and localization and it is not clear if current adoptive immunotherapy protocols can reconstitute the full spectrum of CD8+ T cell immunity. The aim of this review is to briefly summarize the role of these T cell subsets in CMV immunity and to describe how current adoptive immunotherapy practices might affect their reconstitution in patients. The bulk of the CMV-specific CD8+ T cell population is made up of terminally differentiated effector T cells with immediate effector function and a short life span. Self-renewing memory T cells within the CMV-specific population retain the capacity to expand and differentiate upon challenge and are important for the long-term persistence of the CD8+ T cell response. Finally mucosal organs, which are frequent sites of CMV reactivation, are primarily inhabited by tissue resident memory T cells, which do not recirculate. Future work on adoptive transfer strategies may need to focus on striking a balance between the formation of these subsets to ensure the development of long lasting and protective immune responses that can access the organs affected by CMV disease.